PEMBIAYAAN INDUSTRI HALAL OLEH LEMBAGA KEUANGAN SYARIAH - Adzkia, Salsabila; Malahayatie (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
Indonesia has the largest Muslim population in the world. This encourages Indonesian people to choose to live in sharia. Sharia is very closely related to the halal industry. Islamic banking can encourage halal industries in Indonesia. The enthusiasm of the community to run a sharia system, it encourages banks to disburse financing to develop a halal industry. Global economic conditions have indicated and caught a signal that the Islamic the economy began to develop. Halal industries should be developed in all sectors, but this Sharia market share is not yet wide. The halal industry should be able to encourage the share of the Islamic banking market to develop broader Sharia-compliant goods and services. The research method used is a descriptive quantitative method and literature review. From the results of the analysis of the role of banks, it is not limited to financing without training, guidance and usury, but also includes halal regulations, halal consumption of products, halal industry intelligence and lawful governance. The government has a role as a regulator between Islamic banking, business actors and MUI so that the economic potential and halal industries according to Sharia can be realized.